Dynamic sonographic measurements at the carpal tunnel inlet: Reliability and reference values in healthy wrists. Issue 4 (30th July 2013) - Filius, Anika; Korstanje, Jan‐Wiebe H.; Selles, Ruud W.; Hovius, Steven E.R.; Slijper, Harm P.
ABSTRACT Introduction: Reliability and reference values are not well‐established for most dynamic sonographic measurements of the median nerve (MN) and flexor tendons that may be used for diagnosing carpal tunnel syndrome (CTS). Methods: Wrists of 20 healthy participants were imaged using ultrasound. Cines of the carpal tunnel inlet were acquired during hand motion. Based on shape and displacement measurements, intra‐ and interrater reliability and reference values were calculated. Results: Intraclass correlation coefficients (ICCs) for measurements of the MN and most flexor tendons were ≥0.51 for shape parameters and ≥0.71 for displacement parameters. During motion, the MN flattened with ulnar movement, tendons became more circular, and flexor tendons of corresponding fingers moved toward each other. Conclusion: Shape and displacement measurements of the MN and most flexor tendons had reliability results ranging from moderate to excellent. The reference values may be useful for the diagnosis of CTS. Muscle Nerve48: 525–531, 2013